Phenomenological Theory of Electromagnons in Multiferroic Systems - Allende-Prieto, S (American Physical Society, 2025)
We analyze the collective excitations of a magnetoelectric multiferroic material and show that the coupling between magnetization and polarization fluctuations gives rise to hybrid modes - electromagnons - resulting from the mixing of magnons (oscillations of the magnetization field) and polarization waves (ferrons). We characterize their main properties and discuss their potential applications in multiferroic-based technologies. Additionally, we provide a phenomenological framework for these systems, which will be invaluable for describing the dynamics of the multiferromagnetic state. © 2025 American Physical Society.